Popular religiosity: A psycho-sociological study of visiting shrines in Turkey - (:unkn) unknown (My University, 2013)
This paper presents the outcome of a recent field study of the practice of visiting shrines based on 3,003 questionnaires and interviews carried out throughout Turkey, involving 30 shrines in 23 cities. This study is pioneering in that it examines the phenomenon of visiting shrines throughout the country from a psycho-sociological point of view. It seeks to find answers to four basic categorical questions: (1) The sociodemographic strata of visitors. (2) The reasons and motivations for making such visits. (3) The types of rituals performed in the shrines. (4) The level of religious performance and knowledge. In short, the study focuses on 3Ws and 1H: who visits the shrines, why they visit the shrines, what they do in shrines and finally, how they perform rituals? The paper also deals with the relationship between religion and spiritual health by focusing on the contribution of petitionary-prayers to religious coping.